2011
DOI: 10.1111/j.1600-0447.2010.01667.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of cerebello-thalamo-prefrontal structure and neurological soft signs in patients with first-episode psychosis

Abstract: Structural alteration in the cerebello-thalamo-prefrontal network is associated with neurological soft signs in schizophrenia, a candidate network for 'cognitive dysmetria'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 53 publications
4
40
0
2
Order By: Relevance
“…In first-episode patients, impaired motor skills in a pegboard task were related to reduced fractional anisotropy in the anterior thalamic radiation and corticospinal tract [212]. Motor coordination was associated with white matter density in the left inferior frontal gyrus [150 ]and thalamus [154]. Furthermore, actigraphically assessed motor activity in schizophrenia was linked to white matter integrity underneath the SMA [92].…”
Section: Neurobiology Of the Motor System In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…In first-episode patients, impaired motor skills in a pegboard task were related to reduced fractional anisotropy in the anterior thalamic radiation and corticospinal tract [212]. Motor coordination was associated with white matter density in the left inferior frontal gyrus [150 ]and thalamus [154]. Furthermore, actigraphically assessed motor activity in schizophrenia was linked to white matter integrity underneath the SMA [92].…”
Section: Neurobiology Of the Motor System In Schizophreniamentioning
confidence: 99%
“…Indeed, motor deficits as a component of NSSs were found to be associated with gray matter loss in the motor cortices, caudate nucleus, and thalamus (see also online suppl. table 2) [150,151,152,153,154,155]. …”
Section: Neurobiology Of the Motor System In Schizophreniamentioning
confidence: 99%
“…According to previous structural magnetic resonance imaging (MRI) studies, increased NSS scores were found to be related to atrophic processes within the caudate nucleus [7,11,12,13], putamen [7,14], globus pallidus [7,13], thalamus [7,11,12,13,15], cerebellum [12,16], inferior and middle frontal gyri [12], and corpus callosum [17]. Studies using functional MRI techniques reported abnormal activation in the pre- and postcentral gyrus, the premotor area, and the middle and inferior frontal gyri in patients with higher NSS scores [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, motor coordination deficits are negatively correlated with cerebellar white matter volume [11]. Furthermore, there have been found a significant inverse correlation between neurological soft signs scores (NSS) and right cerebellar hemisphere volume [12].…”
Section: Introductionmentioning
confidence: 87%
“…It has been shown that higher scores of motor coordination subscores of NSS are correlated negatively with white matter structure of the cerebellum. Also total NSS scores are associated with altered cerebello-thalamo-cortical network [11] and interestingly with mentioned right cerebellar hemisphere volume, involved in language processesing [39].…”
Section: Discussionmentioning
confidence: 99%